Nociceptive signaling through transient receptor potential vanilloid 1 is regulated by Cyclin Dependent Kinase 5-mediated phosphorylation of T407 in vivo. (29th June 2022) - Cho, Andrew; Hall, Bradford E; Limaye, Advait S; Wang, Sheng; Chung, Man-Kyo; Kulkarni, Ashok B
Cyclin dependent kinase 5 (Cdk5) is a key neuronal kinase whose activity can modulate thermo-, mechano-, and chemo-nociception. Cdk5 can modulate nociceptor firing by phosphorylating pain transducing ion channels like the transient receptor potential vanilloid 1 (TRPV1), a thermoreceptor that is activated by noxious heat, acidity, and capsaicin. TRPV1 is phosphorylated by Cdk5 at threonine-407 (T407), which then inhibits Ca 2+ dependent desensitization. To explore the in vivo implications of Cdk5-mediated TRPV1 phosphorylation on pain perception, we engineered a phospho-null mouse where we replaced T407 with alanine (T407A). The T407A point mutation did not affect the expression of TRPV1 in nociceptors of the dorsal root ganglia and trigeminal ganglia (TG). However, behavioral tests showed that the TRPV1 T407A knock-in mice have reduced aversion to oral capsaicin along with a trend towards decreased facial displays of pain after a subcutaneous injection of capsaicin into the vibrissal pad. In addition, the TRPV1 T407A mice display basal thermal hypoalgesia with increased paw withdrawal latency while tested on a hot plate. These results indicate that phosphorylation of TRPV1 by Cdk5 can have important consequences on pain perception, as loss of the Cdk5 phosphorylation site reduced capsaicin- and heat-evoked pain behaviors in mice.